2023
DOI: 10.3390/separations10030212
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-Based Silica/Calcium Carbonate Nanocomposites for the Adsorptive Removal of Escherichia coli from Aqueous Suspensions

Abstract: The present study deals with the adsorptive removal of Escherichia coli (E. coli) by making use of chitosan-silica/calcium carbonate (CS-SiO2/CaCO3) nanocomposites (NCs) where it was synthesized using the waste eggshells and rice husks occurred by natural sources. The bioadsorbent CS-SiO2/CaCO3 NCs were synthesized by incorporating eggshell-CaCO3 nanoparticles (NPs) and rice husk-SiO2 NPs in chitosan NPs solution. The adsorbents were characterized using HRTEM, BET, DLS, and TGA. The characterization of NCs rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…From the short interaction time, the kinetic study, as shown in Figure 4c, was observed to best follow the pseudo-second-order mechanism with rate constant and removal rate of 2.5 × 10 8 CFU g −1 and 6.3 × 10 23 CFU min −1 , respectively. This demonstrated the highest level of linearity (0.9555) in comparison with the determination by the first-order adsorption model (0.9488), thereby predicting chemisorption as the rate-limiting step describing the adsorption processes [52], thus serving as the best kinetic model to describe the adsorption of E. coli onto TM@ZnO/TMC NC hydrogel, supporting the claim of pseudo-second order, describing the equilibrium of E. coli adsorption onto the surface of NC hydrogel [2,53].…”
Section: Studies Of Adsorption Kineticssupporting
confidence: 55%
See 3 more Smart Citations
“…From the short interaction time, the kinetic study, as shown in Figure 4c, was observed to best follow the pseudo-second-order mechanism with rate constant and removal rate of 2.5 × 10 8 CFU g −1 and 6.3 × 10 23 CFU min −1 , respectively. This demonstrated the highest level of linearity (0.9555) in comparison with the determination by the first-order adsorption model (0.9488), thereby predicting chemisorption as the rate-limiting step describing the adsorption processes [52], thus serving as the best kinetic model to describe the adsorption of E. coli onto TM@ZnO/TMC NC hydrogel, supporting the claim of pseudo-second order, describing the equilibrium of E. coli adsorption onto the surface of NC hydrogel [2,53].…”
Section: Studies Of Adsorption Kineticssupporting
confidence: 55%
“…For the E. coli adsorption study onto ZnO/TMC NC, a modified protocol described in Bwatanglang et al [2] was adopted. A known concentration of TM@ZnO/TMC NC hydrogel in a media containing cultured bacterial cell lines (E. coli) in nutrient broth (NB) was first incubated at 35 • C for 24 h at 100 rpm under continuous shaking conditions.…”
Section: Bacterial Adsorption Studiesmentioning
confidence: 99%
See 2 more Smart Citations